Kinematic analysis of robotic biped locomotion systems - Silva, Filipe M. (2019)
The research interest on biped walking machines have been increasing in recent years because of the many advantages over wheeled vehicles on rough terrain. Legged vehicles can traverse uneven terrain, manoeuvre in confined spaces and climb stairs with a minimum of swinging and lurching. In early work, biped walking has been studied by using simple models (e.g. inverted pendulum models) as approximation to bipeds and then analyzing various methods of control.